Knowledge and practices about hemodialysis among dialysis technicians in western part of India - Manish R Balwani; Jigar Shrimali; Amit Pasari; Jay Shah; Vivek Kute (Society of Diabetic Nephropathy Prevention, 2020)
Introduction: Chronic kidney disease (CKD) is a global health burden with a high economic cost to health systems. Objectives: To determine the knowledge and practices regarding end-stage renal disease and hemodialysis (HD) among dialysis technicians. Patients and Methods: Total of 157 technicians participated in a study carried out at Ahmedabad city of Gujrat state. A validated written questionnaire was distributed among dialysis technicians who gave their consent to participate in the study and responded questionnaires were analyzed. Data entry was made in Excel software in codes and analysis was conducted by SPSS software version 17.0 Results: Out of 157, 113 participants were routinely using online clearance monitoring. Around, 19.1% carried out disinfection of water loop once per week, while 23.6% and 28% were doing it once in 15 days and 30 days respectively. Reverse osmosis (RO) plant parameters like pH, hardness of water, chlorine content were checked once daily by 46.5% of technicians while 17.8% and 24.2% technicians were doing it once a week and once a month respectively. About 87.3% of technicians said that dialyzer was reused at their center. Accordingly, 33.8% and 51.6% of technicians were using formalin and per-acetic based disinfectants for dialyzer reprocessing. Additionally 7.6% of technicians were using hypochlorite as disinfectant at their center. Around 63.7% of technicians said they were not reprocessing dialyzers of HCV positive patients. They preferred to use single dialyzers in these subsets of patients at their center. Around, 79.6% of technicians said that endotoxin filter was installed in their dialysis unit. Likewise, 45.9% knew correctly the permissible level of endotoxin in RO water used for HD. Only 15.3% of technicians had correct knowledge of permissible level of bacteria in treated RO water as per association for the advancement of medical instrumentation (AAMI) standards. Conclusion: Better knowledge and awareness about dialysis standards among dialysis technicians will help in better patient's care. Effective dialysis education campaign needs to be driven at regular intervals with relevant information among dialysis technicians to address the knowledge gap.